Psychometric evaluation of the Malay version of the Impact of Weight on Quality of Life-Lite (IWQOL-LITE) questionnaire - Mohd Rizal Abdul Manaf,; Ahmad Fareed Abdul Rahman,; Aniza Ismail,; Sharifa Ezat Wan Puteh,; Azimatunnoor Aizuddin, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction The availability of obesity specific quality of life measurement tool is limited. The Malay version of Impact of Weight on Quality of Life-Lite is an obesity specific quality of life questionnaire which has been translated for use in Malaysia. The aim of this study is to evaluate the validity and reliability of this questionnaire to measure quality of life among different body mass index (BMI) groups. Methods One hundred and twenty subjects with different BMI categories who attended an outpatient government clinic were recruited for this study. The translated Malay version of IWQOL-Lite was used to assess the impact of weight on quality of life of respondents. Content validity, criterion validity and construct validity were used to assess the questionnaire validity while internal consistencies and test-retest reliability were used to assess the questionnaire reliability. Results The Malay version of IWQOL-Lite showed good psychometric properties. The content validity was agreed upon by expert panels. The mean score of all IWQOL-Lite domains were able to discriminate between different BMI groups. Good internal consistency was demonstrated by Cronbach alpha of 0.936. Test-retest reliability ranged from 0.828 to 0.932. The physical function score (IWQOL-Lite) correlated positively with Physical Component Summary of Short Form-36 questionnaire. Exploratory factor analysis found that the questions loaded on their respective five domains. Conclusions The results suggested that the Malay version of IWQOL-Lite is a valid and reliable tool to measure quality of life among obese and overweight subjects in Malaysia.